2023
DOI: 10.1002/cac2.12417
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic YAP1‐mediated ESCRT‐III assembly promotes autophagic cell death and is ubiquitinated by NEDD4L in breast cancer

Abstract: Background Nuclear Yes1‐associated transcriptional regulator (YAP1) promotes tumor progression. However, the function of cytoplasmic YAP1 in breast cancer cells and its impact on the survival of breast cancer patients remain unclear. Our research aimed to explore the biological function of cytoplasmic YAP1 in breast cancer cells and the possibility of cytoplasmic YAP1 as a predictive marker of breast cancer survival. Methods We constructed cell mutant models, including NLS‐YAP15SA (nuclear localized), YAP1S94A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…On the other hand, CHMP2B is decreased in patients with endometrial carcinoma and the urinary exosomes of patients with colorectal cancer compared to healthy individuals 57 , 58 . Recently, Guo et al revealed that cytoplasmic Yes1-associated transcriptional regulator (YAP1) could inhibit the proliferation of breast tumors by promoting autophagy, potentially through the combination of CHMP2B and VPS4B 59 . However, the experiments conducted and the model constructed in this research were mainly based on YAP1, while the role of CHMP2B itself remained to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CHMP2B is decreased in patients with endometrial carcinoma and the urinary exosomes of patients with colorectal cancer compared to healthy individuals 57 , 58 . Recently, Guo et al revealed that cytoplasmic Yes1-associated transcriptional regulator (YAP1) could inhibit the proliferation of breast tumors by promoting autophagy, potentially through the combination of CHMP2B and VPS4B 59 . However, the experiments conducted and the model constructed in this research were mainly based on YAP1, while the role of CHMP2B itself remained to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Auriculasin [25] Colon Ca ↓ pAIFM1 [25] Bromelain [60] Colon Ca ↑ ATG5, ATG7 [61], ACSL4 [60] Curcumin [62] Colon Ca ↑ ATF3 [63], ACSL4 [64], IREB2 [63], HMOX1 [65] ↓ SLC7A11, GPX4 [62,64], HIF1A [66], NEDD4 [67,68] Dihydroartemisinin [69] Glioma ↑ ATF4 [70,71], NCOA4 [72], HMOX1 [69] ↓ GPX4, SLC7A11, SLC3A2 [70], FTH1 [73] Dihydroisotanshinone I [74] Glioma ↑ ACSL4 [74] ↓ GPX4 [74] Diplacone [75] Lung Ca DMOCPTL [76] Breast Ca ↓ GPX4 [76] Epigallocatechin gallate [77] Pancreatic Ca ↑ ATF4 [78], ATG5, ATG7 [79], YAP1 [80] ↓ SP1, TP53 [81] Epunctanone [82] Leukemia…”
Section: Ferroptosis Inducersmentioning
confidence: 99%
“…For the modulation of ferroptosis-inducing genes, EGCG enhances the ferroptosis of pancreatic cancer cells by promoting the degradation of the ferroptosis-inhibiting GPX4 gene [ 77 ]. For non-ferroptosis responses, EGCG may induce ER stress [ 78 ], autophagy [ 79 , 80 ], and apoptosis [ 79 ]. EGCG triggers the ER stress of colon cancer cells by upregulating the ferroptosis-inducing ATF4 gene [ 78 ].…”
Section: Ferroptosis-modulating Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione peroxidase 4 (GPX4) determines the sensitivity of lung cancer cells to etoposide-induced ferroptosis, and NEDD4L can ubiquitinate GPX4, resulting in its subsequent degradation (Cheng et al, 2023). Cytoplasmic yes-associated protein 1 (YAP1) promotes autophagic death in breast cancer cells, and NEDD4L mediates ubiquitination and downregulation of YAP1 (Guo et al, 2023). Human organic anion transporter 3 (hOAT3) is highly expressed in the kidneys and plays a key role in the secretion of clinically important drugs, including anti-cancer drugs (You, 2002;Erdman et al, 2006).…”
Section: Downstream Substrates Of Nedd4lmentioning
confidence: 99%